Pengaruh Media Promosi Kesehatan terhadap Perubahan Status Gizi Baduta di Desa Paloh Punti Lhokseumawe - Puan Nassya Amalia Islamy; Nora Maulina; Noviana Zara (Lembaga Pengembangan Kinerja Dosen, 2025)
Nutrition is very important in human development and growth. The 2021 edition of UNICEF-WHO-WORLD BANK states that 148.2 million children aged 0-5 years worldwide are stunted, 38.9 million are overweight, and 45.4 million are severely wasted. Nutritional problems often occur at the age of 6-24 months due to inadequate nutrition because of lack of mother's knowledge, therefore it is necessary to carry out interventions to increase mother's knowledge regarding balanced nutrition of children under two. The purpose of this study was to determine the effect of health promotion media on changes in the nutritional status of children under two years in Paloh Punti Village, Muara Satu District, Lhokseumawe. This research method used quasi-experimental quantitative research with a one group pretest-posttest design and involved 51 children under two years. The data collection technique used was purposive random sampling. The data collected is primary data in the form of body weight which is limited to nutritional status based on body weight/age. The results showed that the nutritional status of children under two years was 92.1% in the good nutritional status category after the intervention. The change in nutritional status from malnutrition to normal nutrition from the results of the prostest compared to the pretest was 27.4%. The use of health promotion media has an effect on malnutrition status based on the Wilcoxon test with a p-value of 0.029. The conclusion of this study is that there is an effect of health promotion media on the nutritional status of children under two years in Paloh Punti Village, Muara Satu District, Lhokseumawe.